Issues Identification Process PT. Pelabuhan Tanjung Priok in a Dwelling Time Case - Damayanti, Trie; Komala Erdinaya, Lukiati; Ayu, Inmas (International Journal of Psychosocial Rehabilitation, 2019)
The Dwelling Time case concerning the PT Tanjung Priok Port is a case that made the company affected by the crisis. According to Kriyantono, the so-called crisis is when an issue has been published by the media and will affect the sustainability of the company. A crisis needs to be addressed so that understanding the crisis requires identifying the issue. In identifying an issue, several stages are carried out, namely identifying the issue in the category that is in the issue life cycle and evaluating the issue by predicting the impact that will occur on the company. In this study, the descriptive method was used by utilizing qualitative data obtained from the corporate secretary of PT. Tanjung Priok Port and its staff, as well as the team appointed to conduct media monitoring activities in this dwelling time case. The results obtained in the issue identification process show that PT. Tanjung Priok Port only relies on mass media monitoring, so there is not enough data to try to be associated with the severity of the crisis caused by the case. This port is only carried out because there are cases that stick out in the mass media. The evaluation is not enough to be able to predict the impact that will occur because the analysis is only carried out by a small team; even some intern students who are on duty participate in this analysis process, which structurally cannot be considered as an analyst and policymaker. The conclusion obtained by the process of identifying the issue of dwelling time at PT. Tanjung Priok was not done well, so the company was unable to see to what extent this issue could bring the company into a crisis, and the effect was that the company could not make the issue mitigation program a further strategy to overcome the dwelling time crisis.